Implementasi Media Flash Card dalam Menanamkan Nilai Karakter Religius pada Pembelajaran Membaca Permulaan Anak Usia Dini - Jamiatul Hamidah (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
The method of learning to begin with is conducted by Al-Kautsar Kindergarten teachers which are still conventional in nature. This means that the method used is still monotonous, the teacher uses the lecture method with whiteboard media, markers, and erasers. This is not very interesting for beginning reading learning. The purpose of this study was to describe the application of flash card media to instill the value of religious characters in learning to begin reading in early childhood in Al-Kautsar Kindergarten. The method used is classroom action research. The steps taken in this study are planning, implementation and observation, and reflection. The results showed that the flash card media can improve the ability to read early childhood and is effective for instilling the value of religious character education.bjectives. This is because student motivation is a variable that is influenced by various factors.